2015 Roadmap to Natural Gas and Electric Coordination. Issue 6 (January 2015) - Peters, Greg
<x xml:space="preserve">Abstract</x> December 2014 will end the year with a completely new set of comments and concerns by anyone who has been following the natural gas‐electric power industry coordination situation. Comments should all be in by then regarding the Notice of Public Rulemaking (NOPR) through the Federal Energy Regulatory Commission's (FERC's) Docket Nos. RM14‐2‐000 and others.